3D numerical study of splitter Plate's effect on a flexible cylinder VIV. (1st February 2023) - Liu, He; Han, Xun; Williams, J.J.R.; Xie, Runyu; Lin, Pengzhi
Abstract: In this paper, a cylinder with the splitter plate, which is a complex three-dimensional flexible structure, is numerically investigated by an in-house code called CgLes-Y. The large eddy simulation is used for the turbulence. Several sets of validation cases are carried out, including the flow around a circular cylinder, the flow-induced vibrations of a flexible beam behind a cylinder, as well as the VIV of a 3-D flexible cylinder. The splitter plate is mounted behind the flexible cylinder in order to suppress the vortex-induced vibration (VIV). The effects of splitter plate's length and coverage rate on the VIV are analyzed. In this study, we propose an optimization of the splitter plate's material area, in which situations the cylinder's vibration amplitude and drag coefficient can be greatly reduced, while detailed discussion of suppression effect is presented accordingly. Highlights: Suppression of vortex-induced vibration by a fully flexible three-dimensional complex structure. Performance of the best parameters of the splitter plate with different length and coverage rate. Investigate of suppressing the drag force and displacement of the flexible cylinder by flexible splitter plate. The flow field characteristics and structure motion characteristics under many different working conditions.